(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This study examines the internal organization of syllables and phonotactic constraints across languages, with particular focus on their implications for second language acquisition and phonological theory. The research analyzes how syllable structures vary typologically and how phonotactic rules govern permissible sound combinations within language systems. Exploring both theoretical frameworks and empirical evidence, this study identifies key patterns in syllable formation, sonority sequencing principles, and cross-linguistic variation in phonotactic constraints, while considering their applications in language teaching and speech therapy contexts.